The Implementation of Using Schoology in Foreign Language Teaching Media Class: Students’ Perception - Riska Basri (AL LUGHAWIYAAT, 2022)
This study aims to investigate students’ perceptions towards the use of Schoology platform in Foreign Language Teaching Media class. The participants of this study consist of 26 students from the students of Foreign Language Teaching Media class A in the fifth semester of the academic year 2019/2020. The qualitative data were analyzed by students’ reflection. The results of the research revealed that the students’ responded positively to the use of Schoology in the Foreign Language Teaching Media Class. The students also find out the use of Schoology in Foreign Language Teaching Media Class beneficial for them. The benefits of Schoology is it can help students to access the material or tasks easily and they can send assignments whenever and wherever. The use of Schoology in the classroom still has a weakness that are network connection and need quota. This study implies that, the use of Schoology in the  Foreign Language Teaching Media class should be encouraged in order to improve the students’ motivation in learning and the students can understand the material easily when the teacher explains the material in classroom.